2017
DOI: 10.3892/ijmm.2017.3195
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of neural differentiation of PC12 cells by using Opti-MEM as a basic induction medium

Abstract: The PC12 cell line is a classical neuronal cell model due to its ability to acquire the sympathetic neurons features when deal with nerve growth factor (NGF). In the present study, the authors used a variety of different methods to induce PC12 cells, such as Opti-MEM medium containing different concentrations of fetal bovine serum (FBS) and horse serum compared with RPMI-1640 medium, and then observed the neurite length, differentiation, adhesion, cell proliferation and action potential, as well as the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…The mutations P206S, R303W, and R441H have already been reported to reduce TPH2 activity [11]. However, an in vitro study using PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla [37], showed that the mutation R441H does not impair TPH2 oligomerization [36]. Thus, to further investigate the impact of P206S, R303W, and R441H amino acid substitutions on dimer coordination, we performed MM-PBSA analysis of TPH2 WT and its variants, as well as analyzed the number of hydrogen bonds and hydrophobic contacts formed between the TPH2 monomers throughout the simulations.…”
Section: Plos Onementioning
confidence: 99%
“…The mutations P206S, R303W, and R441H have already been reported to reduce TPH2 activity [11]. However, an in vitro study using PC12 cells, a cell line derived from a pheochromocytoma of the rat adrenal medulla [37], showed that the mutation R441H does not impair TPH2 oligomerization [36]. Thus, to further investigate the impact of P206S, R303W, and R441H amino acid substitutions on dimer coordination, we performed MM-PBSA analysis of TPH2 WT and its variants, as well as analyzed the number of hydrogen bonds and hydrophobic contacts formed between the TPH2 monomers throughout the simulations.…”
Section: Plos Onementioning
confidence: 99%
“…The generation of action potentials is an important physiological property of mature neurons [ 29 , 30 ]. To assess whether action potentials are generated in NSC-34 cells, we performed current-clamp recordings on non-neurite-bearing cells treated with a vehicle for 2 days and neurite-bearing cells treated with PGE 2 (30 μM) for 2 days or RA (10 μM) for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…It was established as a neuron study model early in 1980. [ 46 ] Most studies have investigated the morphology of PC12 cells on electrospun nanofibers rather than gels. The adhesion and proliferation of these cells on PCL/chitosan/polypyrrole electrospun nanofibers was higher than that of pure PCL nanofibers.…”
Section: Discussionmentioning
confidence: 99%